Exosomes Derived from Stem Cells from the Apical Papilla Promote Dentine-Pulp Complex Regeneration by Inducing Specific Dentinogenesis. (27th May 2020) - Zhuang, Xueying; Ji, Lingli; Jiang, Huan; Liu, Yao; Liu, Xuemei; Bi, Jing; Zhao, Weidong; Ding, Zhenjiang; Chen, Xu
Abstract : Regenerative endodontic procedures (REPs) are a new option for the treatment of dental pulp or periapical diseases in permanent teeth with open apices. Histologically, the new tissues formed in the root canal after REPs are mainly cementum- or bone-like mineralised tissues, but not the real dentine-pulp complex. Therefore, how to promote dentine-pulp complex regeneration and improve the clinical effects of REPs has become a prominent research topic. Stem cells from apical papilla (SCAP) are derived from the dental papilla that can differentiate into primary odontoblasts and dental pulp cells that produce root dentine and dental pulp. Exosomes are the key regulator for the paracrine activity of stem cells and can influence the function of recipient cells. In this study, SCAP-derived exosomes (SCAP-Exo) were introduced into the root fragment containing bone marrow mesenchymal stem cells (BMMSCs) and transplanted subcutaneously into immunodeficient mice. We observed that dental pulp-like tissues were present and the newly formed dentine was deposited onto the existing dentine in the root canal. Afterwards, the effects of SCAP-Exo on the dentinogenesis of BMMSCs were elucidated in vitro . We found that the gene and protein expression of dentine sialophosphoprotein and mineralised nodule formation in BMMSCs treated with SCAP-Exo were significantly increased. In summary, SCAP-Exo were endocytosed by BMMSCs and obviously improved their specific dentinogenesis. The use of exosomes derived from dental stem cells could comprise a potential therapeutic approach for dentine-pulp complex regeneration in REPs.